Dampak Profit and Loss Sharing terhadap Biaya Produksi dan Pendapatan: - Mauhibbatus Syakirin; Lilik Rahmawati; Muafi Aulia Rachman; Riyanto Riyanto; Rio Kartika Supriyatna; Sholikul Hadi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The theory of Profit and loss sharing is as a solution outside the interest system that does not reflect fairness because it gives rise to discrimination against profit sharing and risks for economic actors. This research was conducted at Islamic financial institutions, namely BMT NU Banyuates in 2019-2021 using descriptive qualitative analysis. From the results Data analysis shows that the value of BMT NU Banyuates revenue has increased in the year 2019-2021. This also happens to operating expenses that have also increased due to due to an increase in items in load at BMT NU Banyuates. But operating profit on BMT NU Banyuates in the same period also experienced an even quite high increase in 2021 which reached 49%. The application of profit and loss sharing theory is seen as more reflective fairness compared to the instrument of interest. Profit and loss sharing in mudharabah and Musyarakah is the right choice because it is considered enough to boost income for shari'a financial companies/institutions.